2020
DOI: 10.3390/jfb11010003
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Photoaging Effect of Plant Extract Fermented with Lactobacillus buchneri on CCD-986sk Fibroblasts and HaCaT Keratinocytes

Abstract: Ultraviolet (UV) exposure triggers the abnormal production of reactive oxygen (ROS) species and the expression of matrix metalloproteinases (MMPs) that are responsible for photoaging. Probiotics are widely used in healthcare and for immune enhancement. One probiotic, Lactobacillus buchneri is found in Kimchi. This study was aimed at assessing the anti-photoaging effect of plant extracts fermented with L. buchneri (PELB) to develop functional cosmetics. We investigated the anti-photoaging effect of PELB in a UV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 35 publications
(33 reference statements)
1
18
0
Order By: Relevance
“…In vitro study of the effects of plant extracts fermented with Lactobacillus buchneri (PELB) on ultraviolet light (UVB)-induced photoaging process reported that PELB could be useful in the cosmetic industry due to its protective effects against UVB-induced photoaging. PELB works by decreasing elastase activity and increasing type I collagen expression, reducing collagenase activity, and promoting the expression of moisture factor and antioxidant enzymes ( 29 ). Our study product showed a significant and persisting increase in skin elasticity which was expressed in the first two weeks of product application.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro study of the effects of plant extracts fermented with Lactobacillus buchneri (PELB) on ultraviolet light (UVB)-induced photoaging process reported that PELB could be useful in the cosmetic industry due to its protective effects against UVB-induced photoaging. PELB works by decreasing elastase activity and increasing type I collagen expression, reducing collagenase activity, and promoting the expression of moisture factor and antioxidant enzymes ( 29 ). Our study product showed a significant and persisting increase in skin elasticity which was expressed in the first two weeks of product application.…”
Section: Discussionmentioning
confidence: 99%
“…The soybean milk fermented by the B. breve strain has a significant increase in hyaluronic acid (HA) production, as demonstrated in a cellular test on skin cells (keratinocytes). Hyaluronic acid, which contributes to skin hydration and elasticity, is naturally produced in human keratinocytes and fibroblasts [24,25]. The B. breve Yakult strain has the ability to convert isoflavone glycoside from soya into aglycone via βglucosidase [26,27].…”
Section: Soybeanmentioning
confidence: 99%
“…They found that PELB decreased elastase activity and increased type I collagen expression in the UVB-induced photoaging in vitro model, reduced collagenase activity, and promoted the expression of moisture factor and antioxidant enzymes. The study results show that the PELB could be useful in the cosmetic industry due to its protective effects against UVB-induced photoaging [ 26 ]. Notay et al investigated the use of topical Nitrosomonas eutropha for cosmetic improvement of facial wrinkles.…”
Section: Photoaging and Skin Agingmentioning
confidence: 99%